EXPLORING GREEN ECONOMY AWARENESS AMONG TVET INSTITUTION STUDENTS - Nor Syazana Nahwah Mohd Zamri; Nur Adibah Raihan Affendy; Muhamad Sufyan Safwan Mohamad Basir, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
In response to pressing environmental challenges, raising awareness of the green economy among students is critical for sustainable development. This study investigates the level of green economy awareness among students in a TVET institution in Borneo, Malaysia. Using a quantitative descriptive research design, data were collected from 309 students using a structured questionnaire. The analysis revealed a moderate level of awareness of green economy principles and sustainable practices. While students showed enthusiasm for activities such as recycling and reusing materials, participation in broader sustainability initiatives was limited. The study highlights the need for improved educational strategies and institutional support to foster a deeper understanding and active engagement in green economy practices among students. The findings suggest that a significant contribution to the development of environmentally aware future professionals can be made by integrating green economy concepts into the curriculum and extracurricular activities.